Penerapan Metode SOSTAC dalam Strategi Pengembangan Bisnis untuk Meningkatkan Omzet UMKM Viqiqa Family Food di Semarang - Dwi Hanani, Fika; Dewi Sumaryana, Fitriana; Fahmi, Indra (Coopetition : Jurnal Ilmiah Manajemen, 2026)
The development of the food industry in Semarang City is increasingly competitive, marked by the presence of various distinctive culinary brands that take advantage of tourism trends and souvenirs. One of the business actors who participated was Viqiqa Family Food, an UMKM engaged in the production of bread and cakes, especially bolen bananas as the main product. However, in the period 2020–2024, this business experienced a fluctuation in turnover with a significant decrease in 2024 of 16%. The decline was caused by weak digital marketing strategies, limited human resources, and lack of operational efficiency. This condition shows the need for a more structured, adaptive, and sustainability-oriented business development strategy. This research is qualitative descriptive with data collection techniques in the form of observation, interviews, and distribution of questionnaires to customers. The results of the study show that the implementation of SOSTAC is able to provide a comprehensive picture of business conditions and business development directions. The Situation Analysis  stage reveals the position of Viqiqa Family Food in the face of competition and customer characteristics; Objectives set measurable goals through the 5S framework (Sell, Serve, Speak, Sizzle, Save); Strategy results in more precise segmentation, targeting, and positioning designs; Tactics emphasizes the digital marketing mix with reinforcement of online promotions, product innovation, and price adjustments; Action details the implementation of the strategy through content planning, promotion scheduling, and production capacity building; while Control generates evaluation indicators such as customer satisfaction levels, increased turnover, and promotional cost effectiveness. Keywords: SOSTAC, Marketing Strategy, UMKM, Business Development, Sales Turnover.